Optimal hydrogen production in a wind-dominated zero-emission energy system - Weimann, Lukas; Gabrielli, Paolo; Boldrini, Annika; Kramer, Gert Jan; Gazzani, Matteo (Elsevier Ltd, 2021)
The role of hydrogen in future energy systems is widely acknowledged: from fuel for difficult-to-decarbonize applications, to feedstock for chemicals synthesis, to energy storage for high penetration of undispatchable renewable electricity. While several literature studies investigate such energy systems, the details of how electrolysers and renewable technologies optimally behave and interact remain an open question. With this work, we study the interplay between (i) renewable electricity generation through wind and solar, (ii) electricity storage in batteries, (iii) electricity storage via Power-to-, and (iv) hydrogen commodity demand. We do so by designing a cost-optimal zero-emission energy system and use the Netherlands as a case study in a mixed integer linear model with hourly resolution for a time horizon of one year. To account for the significant role of wind, we also provide an elaborate approach to model broad portfolios of wind turbines. The results show that if electrolyzers can operate flexibly, batteries and power-to--to-power are complementary, with the latter using renewable power peaks and the former using lower renewable power outputs. If the operating modes of the power-to--to-power system are limited - artificially or technically - the competitive advantage over batteries decreases. The preference of electrolyzers for power peaks also leads to an increase in renewable energy utilization for increased levels of operation flexibility, highlighting the importance of capturing this feature both from a technical and a modeling perspective. When adding a commodity hydrogen demand, the amount of hydrogen converted to electricity decreases, hence decreasing its role as electricity storage medium.
Keywords: hydrogen economy; power to hydrogen; zero emission; MILP optimization; energy system model; SDG 7 - Affordable and Clean Energy